2021
DOI: 10.1177/0261927x211036171
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Risk Factors: A Language Analysis Approach in Social Media

Abstract: Suicide represents a public health issue that requires new preventive strategies. Therefore, this study analyzes differences in language use between a themed posts group (suicide and depression) and a random posts group (non-specific topics) from different social media platforms. In addition, the similarity of the texts of themed posts group with the set of phrases linked to suicide risk factors is analyzed. Texts were processed using the Linguistic Inquiry and Word Count (LIWC) software. A 95% bootstrap confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 36 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…The research literature on STB has exploded in the past several years with an impressive array of descriptive analyses and modeling efforts aiming to better detect (Renjith et al, 2022), predict (Roy et al, 2020), describe (Sierra et al, 2022), and explain (Unruh-Dawes et al, 2022) suicidal phenomenology through the leverage of online social media and the "big data" afforded by web-based communication platforms. Given the nature of the medium, natural language processing (NLP) has emerged as a prominent analytical tool, effectively paired with a variety of other cutting-edge quantitative approaches such as network analysis (Sawhney et al, 2022) and machine learning (Castillo-Sánchez et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The research literature on STB has exploded in the past several years with an impressive array of descriptive analyses and modeling efforts aiming to better detect (Renjith et al, 2022), predict (Roy et al, 2020), describe (Sierra et al, 2022), and explain (Unruh-Dawes et al, 2022) suicidal phenomenology through the leverage of online social media and the "big data" afforded by web-based communication platforms. Given the nature of the medium, natural language processing (NLP) has emerged as a prominent analytical tool, effectively paired with a variety of other cutting-edge quantitative approaches such as network analysis (Sawhney et al, 2022) and machine learning (Castillo-Sánchez et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Applying a combination of natural language processing (Brown et al, 2019), network analysis (Kemp & Collings, 2011), and machine learning techniques (Tadesse et al, 2020), among others, research has demonstrated the ability to extract meaningful signals of STB from the content and behaviors reflected in online activity. Works have applied and tested prominent suicide theories (Unruh-Dawes et al, 2022), highlighted important semantic features (Sierra et al, 2022), characterized conversational topics (Grant et al, 2018), profiled emotion (Ren et al, 2016), studied information flow (Kemp & Collings, 2011), and probed one or more specific concepts such as stigma (Li et al, 2018), anti-mattering (Deas et al, 2023), and negative social comparison (Spitzer et al, 2023). The richness of the data that drive these endeavors is owed in part to source ubiquity and ease of access, the potential for interactive anonymity, and a temporal density of sampling that typically characterizes a "passively collected" record of internet activity.…”
Section: Introductionmentioning
confidence: 99%
“…Miyagi et al [19] highlighted the potential for social media-based prevention measures to be undermined by the proliferation of offensive opinions and nonpreventive advertisements following a high-profile suicide-related incident. Numerous other studies have corroborated the association between social media use and suicide risk, further emphasizing the need for a comprehensive understanding of this complex relationship [20][21][22][23][24]. Nonetheless, regulating suicide-related information on these platforms is challenging due to the vast number of users and limited oversight.…”
Section: Introductionmentioning
confidence: 99%